An exploratory study of cognitive, social and normative dimensions of female entrepreneurship within transition economies: Evidence from India and Vietnam - Meghna Chhabra; Rajat Gera; Rohail Hassan; Sohail Hasan (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2020)
Prior research conducted on budding female entrepreneurship did not highlight the transition nations such as Asia experiencing relatively faster economic growth and socioeconomic transformation. The role of contextual environment and motivation type in female entrepreneurship has not been adequately researched. This exploratory study of the association between the cognitive, social, and normative determinants of nascent female entrepreneurship activities in the two transition economies of India and Vietnam. This comparative study used the Global Entrepreneurship Monitor (GEM) database of 2015 for data collection. Data analysis of individual surveys from the database was conducted for selected categorical variables by using nonparametric tests of association for cross-tabulation (Chi-square test). The results show that the cognitive, social, and normative factors have a significant role in nascent female entrepreneurial levels in India and Vietnam. Socio-cultural influences play a dominant role in influencing and shaping women's entrepreneurial career choices to start a business. Moreover, women's entrepreneurial intentions is a product of the dynamic interaction of cognitive, social, and cultural factors at the individual (micro), social (meso), and cultural (macro) levels. This comparative country study of two middle-income transition South Asian economies creates insight into the gender and motivation specific contextualized roles of cognitive creates insight into the gender and motivation specific contextualized roles of cognitive and normative factors associated with nascent entrepreneurship at the country level. No prior other study has evaluated the contextualized role of women entrepreneurship's cognitive and social determinants by comparing two countries with similar economic and socio-cultural environments. The findings of the study can be used by policymakers to make better-informed decisions to promote women entrepreneurs by curating contextspecific policies.
Keywords: 330; female entrepreneurship; gender gap; opportunity entrepreneurship; necessity entrepreneurship; nascent entrepreneurship; transition economies; middle-income countries